Mefloquine treatment for uncomplicated falciparum malaria in young children 6-24 months of age in northern Ghana. - Fryauff, D. J.; Owusu-Agyei, S.; Utz, G.; Baird, J. K; Koram, K.A.; Binka, F.; Nkrumah, F.; Hoffman, S. L. (My University, 2007)
Mefloquine (MQ) single dose 20 mg/kg treatment of falciparum malaria was evaluated in 186 children of 6-24 months of age in northern Ghana. There were 15 RII/RIII-type parasitologic failures, all with Day 2 MQ blood levels significantly lower than children whose parasitemias cleared before Day 7 and remained clear through 28 days. Predictors of RII/RIII parasitologic response were vomiting after MQ dosing, Day 2 MQ levels < 500 ng/mL, and undetectable Day 2 levels of the carboxymefloquine metabolite. There were 50 cases of delayed RI parasitologic failure, but 71% of these cases had undetectable Day 28 blood levels of MQ and drug levels in the remaining 29% ranged below the 620 ng/mL level that suppresses MQ sensitive strains of P. falciparum. Drug levels among infants that tolerated MQ well were not associated with age, weight, hemoglobin, parasitemia, and pre-existing symptoms of vomiting or diarrhea. An observed recurrent parasitemia of 34,400 trophozoites/μL against a MQ blood concentration of 550 ng/mL was taken as indication of tolerance to suppressive levels of the drug at this location. Copyright © 2007 by The American Society of Tropical Medicine and Hygiene.
Keywords: EMTREE drug terms: hemoglobin; mefloquine; antimalarial agent EMTREE medical terms: article; controlled study; drug blood level; drug tolerability; female; Ghana; human; infant; major clinical study; malaria falciparum; male; parasitemia; preschool child; single drug dose; treatment failure; animal; blood; chemically induced disorder; clinical trial; cohort analysis; diarrhea; growth, development and aging; parasitology; Plasmodium falciparum; prospective study; statistical model; vomiting